Early Endoscopic Outcomes After Risankizumab Are Associated With Fewer Hospitalizations and Surgeries in Crohn’s Disease - Brian G. Feagan; Jean-Frederic Colombel; Remo Panaccione; Stefan Schreiber; Marc Ferrante; Koji Kamikozuru; Christopher Ma; Wan-Ju Lee; Jenny Griffith; Namita Joshi; Kristina Kligys; Jasmina Kalabic; et al. (Gastro Hep Advances)
Background and Aims: We evaluated the association between endoscopic outcomes following risankizumab induction and subsequent rates of hospitalization and surgery through 52 weeks of risankizumab (both doses) maintenance therapy in patients with Crohn’s disease (CD). Methods: Patients with moderately to severely active CD and clinical response to 12-week risankizumab induction were rerandomized to continued therapy or drug withdrawal in the phase 3 FORTIFY maintenance trial. Incidence rates (events/100 person-years) of CD-related hospitalization and surgery, and the composite of both, through 52 weeks of maintenance were compared between patients achieving vs not achieving predefined endoscopic outcomes following induction. Results: Patients who achieved vs did not achieve endoscopic response or remission, or absence of ulcers (ulcer-free endoscopy) after induction had reduced rates of CD-related hospitalization through 52 weeks of risankizumab maintenance (endoscopic response, 1.7 vs 7.9/100 person-years; endoscopic remission, 1.2 vs 6.9/100 person-years; ulcer-free endoscopy, 1.5 vs 6.4/100 person-years; all P < .05). No CD-related surgeries were observed through 52 weeks of risankizumab maintenance among patients who achieved vs did not achieve endoscopic outcomes following induction (endoscopic response, 0 vs 3.2/100 person-years; endoscopic remission, 0 vs 2.6/100 person-years; ulcer-free endoscopy, 0 vs 2.4/100 person-years; all P = .025). In contrast, patients who received placebo during maintenance had statistically similar rates of CD-related hospitalizations and surgeries regardless of achievement of endoscopic outcomes after induction. Conclusion: Patients achieving endoscopic outcomes following risankizumab induction experienced less CD-related hospitalizations and surgeries through 52 weeks of maintenance when continuing active therapy. Early treatment success may predict favorable long-term outcomes of disease.